ON THE QUESTION OF WORDS DESIGNATING THE CONCEPT OF ‘FAMILY’IN THE KAZAKH LANGUAGE (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
This article presents the results of a study of words with the nuclear seme 'family' in the Kazakh language. It is noted that the words tütün, şañıraq and tündik (tündük) have evolved into synonyms in their secondary meanings, defining the family as a subject of economic activity. Also in the Kazakh language there was an izafet phrase tündik bası, which in grammatical structure and compositional semantics is similar to the expression ot bası. Attention is drawn to the fact that the concept of “family” as an elementary socio-economic complex in the Kazakh language was expressed by such paired words as mal-jan, üy-jay, and the separation of married sons from the father’s hearth and the creation of new families was designated by the words üy bol-, üy köter-. It is emphasized that the development of new lexical meanings occurred through a series of successive metonymic transfers in time and space of two phenomena or objects (a group of residents and a lit hearth).The need for a word with a strictly defined meaning of ‘a group of close relatives living together’ led to the emergence of a new lexical formation in the language, jan uya, which is metaphorical and is found in an artistic style of speech that allows the use of poetic images.As a result of changes in socio-economic conditions, there arose a need for a word that would designate the family as a new social formation and would have content (‘a group of relatives living together’ (husband and wife, parents and children), would correspond to legal relations and would be free from additional semantic nuances. The authors believe it is appropriate to introduce the use of the word äyile into linguosocial practice, the presence of which corresponds to the cultural and historical tradition of replenishing the lexical fund with borrowings from the Arabic language and will contribute to maintaining the closeness of the literary languages ​​of the Turkic peoples.